A rare clinical entity of asymptomatic adult bochdalek hernia - Ramachandran, Balamurugan; Pugazhenthi, Aravindan Srinivasan; Bharadwaj Rajkumar, Abhinav; Dube, Saumitra; Perumal, Moorthy (International Surgery Journal, 2020)
Bochdalek hernia (BH) is the commonest congenital diaphragmatic hernia, caused by the failure of the posterolateral diaphragmatic foramina to fuse properly. It is extremely rare in adults and accounts for 5-10%. Presenting a case of 48 years female with complaints of dry cough and left chest pain for 1 week. Diminished breath sounds and abnormal gurgling sounds heard on auscultation of left chest wall. X-ray chest showed elevated left hemi diaphragm and gastric bubble. Computed tomography (CT) chest revealed left diaphragmatic hernia with splenic flexure, transverse colon, mesocolon, spleen and upper pole of left kidney as content and atelectasis of left lung lower lobe. Patient underwent laparoscopic repair of hernia with mesh plasty. Intraoperatively, the contents were reduced into the abdominal cavity and left lung expansion noted. The defect of size 6×10 cm in the left diaphragm was sutured and composite mesh placed. Post-operative chest x-ray showed expanded left lung. On follow up of patient after 2 weeks and 1 month, patient was asymptomatic. BH in adults is an uncommon. The contents can be reduced via thoracic or abdominal approach, with abdominal approach having easier access. With the advent of minimal access techniques, delineating clear anatomy, more working space, early recovery, and early return to home and work is possible. Thus, laparoscopic repair of adult diaphragmatic hernia is a safe and effective modality of surgical treatment.